2020
DOI: 10.1039/c9sm01837a
|View full text |Cite
|
Sign up to set email alerts
|

Particle diffusion in extracellular hydrogels

Abstract: We show that the diffusivity of particles in biomimetic extracellular hydrogels based on hyaluronan depends on the stress relaxation dynamics of the hydrogel and is strongly affected by the presence of collagen fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 83 publications
0
34
0
Order By: Relevance
“…Previous single-molecule studies reported similar distributions and fit them to the sum of a single Gaussian, to capture small displacements, and an exponential function, to capture the large "tails" in the distributions. 59,67,68,92 The exponential portion of the van Hove function can be described by G exp Δx, t ∝ exp − Δx λ t where λ(t) is the time dependent decay length of the system. This characteristic decay length λ(t) can be understood as an average of length scales associated with each of the relaxation processes that contribute to the exponential tail of the distributions.…”
Section: Heterogeneous and Non-ergodic Transportmentioning
confidence: 99%
“…Previous single-molecule studies reported similar distributions and fit them to the sum of a single Gaussian, to capture small displacements, and an exponential function, to capture the large "tails" in the distributions. 59,67,68,92 The exponential portion of the van Hove function can be described by G exp Δx, t ∝ exp − Δx λ t where λ(t) is the time dependent decay length of the system. This characteristic decay length λ(t) can be understood as an average of length scales associated with each of the relaxation processes that contribute to the exponential tail of the distributions.…”
Section: Heterogeneous and Non-ergodic Transportmentioning
confidence: 99%
“…While the smaller anomalous scaling exponent found in SPT analysis (Fig. 2) indicates more subdiffusion, a smaller stretching exponent represents a wider distribution of decay times that is indicative of more heterogeneity in the environment 37,38,40 . This trend supports our displacement distribution data (Fig.…”
mentioning
confidence: 90%
“…Anomalous transport dynamics manifest in DDM measurements in the form of intermediate scattering functions (ISF) fit by stretched exponentials [37][38][39] or ISFs that do not decay to zero, but have a non-zero plateau [39][40][41] -hallmarks of heterogeneity and nonergodicity, respectively. We previously showed that varying the relative concentrations of actin and microtubules in entangled actin-microtubule composites (without crosslinkers) led to surprising and complex effects on particle transport in these networks 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicated that the microsphere diffusivity depends on the microsphere size relative to the network pore size and also on the stress relaxation dynamics of the network. The diffusion of nutrients, growth factors and other molecules in hydrogel can change depending the degree of crosslinking (Burla et al, 2020). Studies also indicated that the concentration of GelMA and its degree of crosslinking are inversely proportional to the degree of porosity and the network pore size, and the decrease of gel concentration is correlated with decreased stiffness of the gel, which promotes cell proliferation and survival (Cuvellier et al, 2021); [45].…”
Section: Discussionmentioning
confidence: 99%